Novel hierarchical nonlinear control algorithm to improve dissolved oxygen control in biological WWTP. (September 2021) - Piotrowski, Robert; Sawicki, Hubert; Żuk, Konrad
Abstract: Wastewater treatment is a problem known to humankind for centuries. The quality of treated sewage determines the condition of reservoirs around the world. Control of such a complex and nonlinear system as a wastewater treatment plant requires thorough knowledge of the process. The paper presents a hierarchical control system of a Sequencing Batch Reactor (SBR) in Wastewater Treatment Plant (WWTP) taking into account a model based on actual measurements taken from a WWTP in Swarzewo, Poland. The authors designed and implemented a nonlinear model predictive controller (MPC) that allows for the optimal implementation of the desired DO level while minimising the operation of actuators (aeration system). The design description of the predictive controller was associated with the need to specify the performance function and define the optimisation problem. In a two-layer structure, a supervisory controller was implemented based on an actual time-based controller in Swarzewo WWTP. The overview showed the improved performance of the treatment plant and the versatility of the created solution. Results of simulation tests for the wastewater treatment plant case study are presented. Highlights: Dissolved oxygen control is very important for WWTP energy efficiency. The process of designing a hierarchical control system of a SBR has been presented. Nonlinear MPC has been applied for optimal implementation of the set DO trajectory. Results of simulation tests for WWTP case study have been presented.